Efektivitas Aromaterapi Mawar Dalam Menurunkan Tingkat Kecemasan Pada Ibu Hamil Primigravida Trimester III - Kasih Bene Gollu; Rosyida Alfitri; Tut Rayani Aksohini Wijayanti (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2026)
Anxiety often occurs before childbirth, and one non-pharmacological therapy that can be used to help reduce anxiety among third-trimester primigravida pregnant women is rose aromatherapy. This study aimed to determine the effectiveness of rose aromatherapy in reducing anxiety levels among third-trimester primigravida pregnant women. This study used a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 22 respondents, divided into 11 respondents in the intervention group and 11 respondents in the control group, selected using consecutive sampling. The instrument used was the Pregnancy-Related Anxiety Questionnaire-Revised 2 (PRAQ-R2). After the intervention, 7 respondents (63.6%) in the intervention group experienced mild anxiety and 4 respondents (36.4%) experienced moderate anxiety, with no respondents experiencing severe anxiety. In the control group, 10 respondents (90.9%) experienced moderate anxiety and 1 respondent (9.1%) experienced severe anxiety. The Independent T-Test showed a significant difference in anxiety reduction between the intervention and control groups, with a p-value